Type I Interferon Induced and Antagonized by Foot-and-Mouth Disease Virus - Ma, Xiao-xia; Ma, Li-na; Chang, Qiu-yan; Ma, Peng; Li, Lin-Jie; Wang, Yue-ying; Ma, Zhong-ren; Cao, Xin (Frontiers in Microbiology, 2018)
Viral infections trigger the innate immune system, serving as the first line of defense, and are characterized by the production of type I interferon (IFN). Type I IFN is expressed in a broad spectrum of cells and tissues in the host and includes various subtypes (IFN-α, IFN-β, IFN-δ, IFN-ɛ, IFN-κ, IFN-τ, IFN-ω, IFN-ν, and IFN-ζ). Since the discovery of type I IFN, our knowledge of the biology of type I IFN has accumulated immensely, and we now have a substantial amount of information on the molecular mechanisms of the response and induction of type I IFN, as well as the strategies utilized by viruses to evade the type I IFN response. Foot-and-mouth disease virus (FMDV) can selectively alter cellular pathways to promote viral replication and evade antiviral immune activation of type I IFN. RNA molecules generated by FMDV are sensed by the cellular receptor for pathogen-associated molecular patterns (PAMPs). FMDV preferentially activates different sensor molecules and various signal transduction pathways. Based on knowledge of the virus or RNA pathogen specificity as well as the function-structure relationship of RNA sensing, it is necessary to summarize numerous signaling adaptors thatare reported to participate in the regulation of IFN gene activation.